2011
DOI: 10.1093/carcin/bgr230
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblasts in omentum activated by tumor cells promote ovarian cancer growth, adhesion and invasiveness

Abstract: Omentum metastasis is a common occurrence in epithelial ovarian cancer (EOC), which is often accompanied by ascites that facilitates the spread of EOC cells. A subpopulation of fibroblasts-the cancer-associated fibroblasts (CAFs) are important promoters of tumor progression. We have shown previously that CAFs exist not only in omentum with EOC metastasis but also in omentum without metastasis. In the present study, using primary human fibroblasts isolated from normal omentum (NFs) and omentum with ovarian canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
137
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 161 publications
(139 citation statements)
references
References 40 publications
2
137
0
Order By: Relevance
“…For example, it was showed that cytokines present within medium conditioned by an ovarian clear cell carcinoma cell line, ES-2, induced urokinase-type plasminogen activator (uPA) mRNA transcription in fibroblast cells, which is a protease implicated in cancer invasion and migration (45). Moreover, a recent study suggested that a premetastatic niche is created in the omentum through the activation and proliferation of NFs that are stimulated by the release of TGF-b1 from cancer cells (46). The establishment of the premetastatic niche would provide an altered microenvironment that enhances tumor invasion and implantation on peritoneal surfaces, through the secretion of hepatocyte growth factor (HGF) and MMP-2 (MMP2; ref.…”
Section: Cancer-associated Fibroblastsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, it was showed that cytokines present within medium conditioned by an ovarian clear cell carcinoma cell line, ES-2, induced urokinase-type plasminogen activator (uPA) mRNA transcription in fibroblast cells, which is a protease implicated in cancer invasion and migration (45). Moreover, a recent study suggested that a premetastatic niche is created in the omentum through the activation and proliferation of NFs that are stimulated by the release of TGF-b1 from cancer cells (46). The establishment of the premetastatic niche would provide an altered microenvironment that enhances tumor invasion and implantation on peritoneal surfaces, through the secretion of hepatocyte growth factor (HGF) and MMP-2 (MMP2; ref.…”
Section: Cancer-associated Fibroblastsmentioning
confidence: 99%
“…The establishment of the premetastatic niche would provide an altered microenvironment that enhances tumor invasion and implantation on peritoneal surfaces, through the secretion of hepatocyte growth factor (HGF) and MMP-2 (MMP2; ref. 46). An inhibitor of the TGF-b type I receptor, A83-01, abrogated TGF-b1 signaling and reduced the proliferation and activation of NFs, as well as reduced a-SMA and MMP-2 expression in SKOV3/NF tumors (46).…”
Section: Cancer-associated Fibroblastsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, stromal components were shown to promote the malignant behavior of pancreatic cancer cells, with myofibroblasts being the especially associated with cancer-stromal cell interactions in primary tumors (7,(9)(10)(11)(12). Few studies, however, assessed cancer-stromal cell interactions at peritoneally disseminated sites (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the interactions between cancer cells derived from the primary tumor and submesothelium layer components such as myofibroblasts may be a key to peritoneal dissemination (24). Hepatocyte growth factors (HGF) produced by human peritoneal myofibroblasts have been found to promote the peritoneal dissemination of gastric cancer (25), and myofibroblasts in omentum were shown to be activated by tumor cells and to promote the growth, adhesion and invasiveness of ovarian cancer (14). However, the roles of peritoneal myofibroblasts and their matrices in the peritoneal dissemination of pancreatic cancer remain unclear.…”
Section: Introductionmentioning
confidence: 99%